The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1021/ja00305a068
|View full text |Cite
|
Sign up to set email alerts
|

Actinobolin via the anomeric effect

Abstract: Actinobolin (la), isolated by Haskell and Bartz2 in 1959 from cultures of Streptomyces griseoviridies var. atrofacienes, found little favor as an antibiotic, one reason being the fact that it was not readily absorbed through the stomach walls. This demerit, coupled with the subsequent discovery that the antibiotic hardens enamel,3 has caused a reawakening of interest in actinobolin as a cariostatic agent. The discovery, 20 years later, of the antitumor agent bactoboiin,4 structurally related although not a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Although the addition to the C5 5N bond of imines, hydrazones and oximes are well known, [3] the development of such reaction is often limited by the poor electrophilicity of the C5 5N carbon atom. Numerous new reagents have been developed for the reduction of oximes to amines including NaBH4, [3,4] LiAlH 4 [5,6] and indium/acetic acid. [7] Though some of these are widely used, still they have limitations based on chemo-selectivity and economic considerations.…”
Section: Reprintsmentioning
confidence: 99%
“…Although the addition to the C5 5N bond of imines, hydrazones and oximes are well known, [3] the development of such reaction is often limited by the poor electrophilicity of the C5 5N carbon atom. Numerous new reagents have been developed for the reduction of oximes to amines including NaBH4, [3,4] LiAlH 4 [5,6] and indium/acetic acid. [7] Though some of these are widely used, still they have limitations based on chemo-selectivity and economic considerations.…”
Section: Reprintsmentioning
confidence: 99%
“…These compounds proved to be versatile substrates in dipolar, photochemical and Diels-Alder cycloadditions. Thus, 1,3-dipolar cycloaddition of diazomethane to enone 74f took place at room temperature in ethyl ether and led to pyrano-pyrazoline 101 in [83] also underwent smooth addition to enone 106 to generate adduct 108 in high yield (Scheme 25d) [84]. Both DielsAlder additions took place exclusively from the -face.…”
Section: Cycloaddtion Reactions Of -Enonesmentioning
confidence: 99%
“…The fact that the ethoxy group in 109a is axial suggested that the anomeric effect, that had already controlled the stereochemistry of the cycloaddition, was also responsible for this preferred conformation. The actinobolin synthesis by Rahman and Fraser-Reid took full advantage of these issues [84].…”
Section: Actinobolin Via the Anomeric Effect Of An Annulated Pyranosidementioning
confidence: 99%
See 1 more Smart Citation
“…2 Therefore, direct transformation of epoxides to the 1,2-diacetates is a very attractive reaction. A review of the literature shows that this transformation has been achieved with the reaction of epoxides and acetic anhydride in the presence of catalysts or reagents such as HCl, ZnCl2, 3 (NH4)3(PMo12O40)6, 4 (TBA)4PFeW11O39·3H2O, 5 Cp2TiCl2, 6 (n-Bu)4NOAc, 7 11-13 and 15), and the others were limited in scope. Some of the previously-reported studies required expensive, exotic or hazardous reagents, extended reaction times, and/or limitation to a narrow range of epoxides.…”
Section: Introductionmentioning
confidence: 99%